Pd-Catalyzed Allylic Alkylation of CF3-Containing Esters with Three Electron-Withdrawing Groups - Li, Lun; Huang, Donghui; Chen, Qing-Yun; Guo, Yong (Synlett, 2013)
Tsuji–Trost reaction (Pd-catalyzed allylic alkylation) of CF3-containing esters with three electron-withdrawing groups is reported. The reactions with methyl bis(trifluoromethyl)acetate and dimethyl (trifluoromethyl)malonate were carried out with low-loading catalysts of Pd(0) and XPhos at ambient temperature in THF, giving the products in high yields. This method efficiently overcomes the β-defluorination, which is hard to control in the chemical transformation of α-trifluoromethyl carbanions, and provides versatile fluorinated compounds with quaternary carbon centers, which are highly demanded in drug discovery.
Keywords: fluorine; carbanions; allylation; palladium; homogeneous catalysis